Source Processes of the March 2007 Singkarak Earthquakes Inferred from Teleseismic Data - Afnimar; Reiji Kobayashi; Danny Hilman Natawidjaja (Journal of Mathematical and Fundamental Sciences, 2014)
The rupture processes of two sequentialearthquakes have been inverted from teleseismic data. The first event released a total seismic moment of 7.9×1018 Nm (Mw 6.5) and the slip distribution shows three asperities, 1.5 m at the shallowside, 0.7 m at the rightsouth-east deep side and 0.5 m atthe north-west deep side. The second event had one asperity with 1.7 m slip and released a seismic moment of 7.5×1018 Nm (Mw 6.5). In both cases, maximum slip occurred above the hypocenter which was responsible for the surface displacement pattern.